CROP ALERT: A Citrus Canker Fact Sheet for Homeowners - H. L. Chamberlain; Pamela D. Roberts; Lavern W. Timmer; Kuang-Ren Chung; Mongi Zekri (EDIS)
Citrus canker (CC) is caused by the bacterial pathogen Xanthomonas axonopodis pv. citri. The pathogen enters host tissues through wounds and natural openings called stomata. It is a serious disease of all citrus and some citrus relatives. This document is PP194, one of a series of the Plant Pathology Department, Florida Cooperative Extension Service, Insitute of Food and Agricultural Sciences, University of Florida. Original Publication Date: September 2001. Reviewed: June 2003.